Consider the integral $(1)$

$$\text{Conjecture}\ \int_{-\infty}^{+\infty}{\mathrm dx\over x^2}\left(1-{\sin x\over x}\right)^n=\color{blue}{\pi\over n+1}\tag1$$ Where $n\ge1$

Required help to prove conjecture $(1)$

An attempt:

Apply binomial series to $(1)$, then we have

$$\sum_{k=0}^{n}(-1)^k{n\choose k}\int_{-\infty}^{+\infty}{x^{n-k}\sin^k x\over x^2}\mathrm dx\tag2$$

We can apply the trick of $(3)$

$$\int_{-\infty}^{+\infty}f(x){\sin^2 x\over x^2}\mathrm dx=\int_{0}^{\pi}f(x)\mathrm dx\tag3$$ then $(2)$ becomes $$I_k=\sum_{k=0}^{n}(-1)^k{n\choose k}\int_{0}^{\pi}{x^{n-k}\sin^{k-2} x}\mathrm dx\tag4$$

I guess we could apply integration by parts to $(4)$ but seem difficult...

  • 6
    $\begingroup$ Wolfram gives the value $\frac{5\pi}{16}$ for $n=3$, so the conjecture is false. $\endgroup$ – uniquesolution Mar 27 '17 at 10:30
  • 2
    $\begingroup$ ... for $n=4$ we have $\frac{19\pi}{60}$, for $n=5$ we have $\frac{383 \pi }{1152}$. $\endgroup$ – Jack D'Aurizio Mar 27 '17 at 10:48
  • $\begingroup$ In (2) the integral $\int_{-\infty}^{\infty} \dfrac{x^{n-k}\sin^{k}x}{x^2}\, dx$ ought to be $\int_{-\infty}^{\infty} \dfrac{x^{-k}\sin^{k}x}{x^2}\, dx$ which diverges. $\endgroup$ – JanG Mar 27 '17 at 11:22
  • 2
    $\begingroup$ All your recent questions are about more or less the same type of integrals (this one being very close to the one you asked 15 hours ago (math.stackexchange.com/q/2204250)). Could you say why you are interested in this type of integrals more than others ? Do you have a textbook with a list of integrals to be computed ? A friendly advice: don't spend too much time on it : till a certain point, you learn analysis techniques, but beyond, it can become rather sterile... $\endgroup$ – Jean Marie Mar 27 '17 at 12:26
  • 1
    $\begingroup$ I got the value $\displaystyle - 4\pi\sum_{k=1}^{n}\binom{n}{k}\cdot\sum_{j=1+\lfloor k/2\rfloor}^{k}\binom{k}{j}(-1)^{j}\dfrac{(j-\frac{k}{2})^{k+1}}{(k+1)!}$. $\endgroup$ – JanG Mar 27 '17 at 19:35

If we define the Fourier transform via \begin{equation*} \hat{f}(\xi) = \int_{-\infty}^{\infty}e^{-i\xi x}f(x)\, dx \end{equation*} we get \begin{equation*} \int_{-\infty}^{\infty}\dfrac{1}{x^2}\left(1-\dfrac{\sin x}{x}\right)^n \, dx = \hat{f}(0) \end{equation*} where \begin{equation*} f(x) = \dfrac{1}{x^2}\left(1-\dfrac{\sin x}{x}\right)^n. \end{equation*} The rest of the answer is concentrated on determining $\hat{f}(0).$

Write \begin{equation*} x^2f(x) = 1+\sum_{k=1}^{n}\binom{n}{k}(-1)^{k}g_{k}(x)\tag{1} \end{equation*} where \begin{equation*} g_{k}(x) = \dfrac{\sin^kx}{x^k}. \end{equation*} It is well known that $\hat{g_{1}}(\xi) =\pi(H(\xi +1)-H(\xi -1))$, where $H$ is the Heaviside function. For $k\ge 2$ we study \begin{equation*} x^kg_{k}(x) = \sin^kx = (2i)^{-k}\sum_{j=0}^{k}\binom{k}{j}(-1)^{j}e^{i(k-2j)x}. \end{equation*} Hence \begin{equation*} i^{k}\hat{g_{k}}^{(k)}(\xi) = 2\pi(2i)^{-k}\sum_{j=0}^{k}\binom{k}{j}(-1)^{j}\delta(\xi-k+2j).\tag{2} \end{equation*} Then we integrate (2) $k$ times. We have to add a polynomial $p_{k}(\xi)$. \begin{equation*} \hat{g_{k}}(\xi) = p_{k}(\xi)+2\pi\cdot(-2)^{-k}\sum_{j=0}^{k}\binom{k}{j}(-1)^{j}\dfrac{(\xi-k+2j)^{k-1}}{(k-1)!}H(\xi-k+2j).\tag{3} \end{equation*} But for $k\ge 2$ $g_{k}\in L_{1}({\mathbb{R}})$. According to Riemann-Lebesgue's lemma $\displaystyle\lim_{\xi\to -\infty}\hat{g_{k}}(\xi) = 0$. But for $\xi < 0$ all Heaviside terms in (3) are $0$. Consequently $\displaystyle \lim_{\xi\to -\infty}p_{k}(\xi) = 0$ which means that $p_{k}(\xi) = 0$ for all $\xi$. We notice that even $\hat{g_{1}}(\xi)$ is included in (3). We are now prepared to return to (1). Fourier transformation yields \begin{gather*} -\hat{f}^{''}(\xi) = 2\pi\delta(\xi) + \sum_{k=1}^{n}\binom{n}{k}(-1)^{k}\hat{g_{k}}(\xi)=\\[2ex] 2\pi\delta(\xi) + 2\pi\sum_{k=1}^{n}\binom{n}{k}(-1)^{k}(-2)^{-k}\cdot\sum_{j=0}^{k}\binom{k}{j}(-1)^{j}\dfrac{(\xi-k+2j)^{k-1}}{(k-1)!}H(\xi-k+2j). \end{gather*} In the next step we integrate twice, change the signs and remove a polynomial of degree one. We get \begin{equation*} \hat{f}(\xi) = -2\pi\xi H(\xi)- 2\pi\sum_{k=1}^{n}\binom{n}{k}2^{-k}\cdot\sum_{j=0}^{k}\binom{k}{j}(-1)^{j}\dfrac{(\xi-k+2j)^{k+1}}{(k+1)!}H(\xi-k+2j). \end{equation*} Finally we put $\xi = 0$.

\begin{gather*} \hat{f}(0) = - 2\pi\sum_{k=1}^{n}\binom{n}{k}2^{-k}\cdot\sum_{j=0}^{k}\binom{k}{j}(-1)^{j}\dfrac{(2j-k)^{k+1}}{(k+1)!}H(2j-k)=\\[2ex] - 4\pi\sum_{k=1}^{n}\binom{n}{k}\cdot\sum_{j=1+\lfloor k/2\rfloor}^{k}\binom{k}{j}(-1)^{j}\dfrac{(j-\frac{k}{2})^{k+1}}{(k+1)!}. \end{gather*}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.